2016
DOI: 10.1080/15504263.2016.1145778
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Substance Use During Cognitive Enhancement Therapy: An 18-Month Randomized Feasibility Study

Abstract: Objective Substance use problems are common among people with schizophrenia, as are significant cognitive impairments. Because of potential shared neurobiological pathways, it is possible that cognitive remediation interventions may be associated with improvements in both substance use and cognition. This study examined the impact of cognitive remediation on alcohol and cannabis use, and the cognitive correlates of changes in substance use among outpatients with schizophrenia. Methods Individuals with schizo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 48 publications
(51 reference statements)
1
18
0
Order By: Relevance
“…Since the association between OFC and insula abnormalities and MS appear to be mediated by cognitive deficits, cognitive remediation, aiming to diminish unhealthy lifestyles might be of help. Cognitive remediation has shown improvements in eating behaviour and weight reduction and reductions in substance use , although these associations have not been investigated yet in relation to MS. In addition, in the former study, the association between cognitive remediation and substance use was not specifically investigated in patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Since the association between OFC and insula abnormalities and MS appear to be mediated by cognitive deficits, cognitive remediation, aiming to diminish unhealthy lifestyles might be of help. Cognitive remediation has shown improvements in eating behaviour and weight reduction and reductions in substance use , although these associations have not been investigated yet in relation to MS. In addition, in the former study, the association between cognitive remediation and substance use was not specifically investigated in patients with schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has become evident that it may also be useful in the fairly common situation where substance use is comorbid with schizophrenia (Sofuoglu et al ). For example, a recent study showed that CET improved the rate of substance abuse in patients with schizophrenia (Eack et al , ). It has also been shown to be effective in improving cognition for veterans with alcohol‐use disorder (Bell et al ).…”
Section: Cognitive Enhancing Agents May Facilitate Behavioral Therapymentioning
confidence: 99%
“…A recent study delivered 12 two-hour group sessions of clinician-guided CRT and computerized CT (Lumosity) (156) over 4 weeks to a sample of female residents completing residential rehabilitation and found significant improvements in EF, response inhibition, selfcontrol, and quality of life relative to treatment as usual (TAU) (157). Similar research has reported comparable improvements in cognitive functioning following CRT (150,151) and CET (148), and improved cognitive functioning has been associated with reduced substance use at 3-and 6-month follow-ups (148,150). Importantly, CET and CRT also demonstrate preliminary efficacy for SUD patients with cognitive impairments (e.g., schizophrenia, past head injury) (148,157).…”
Section: Cognitive Remediationmentioning
confidence: 96%
“…In SUD, general cognitive remediation approaches such as cognitive enhancement therapy (CET) and cognitive remediation therapy (CRT) aim to reduce substance use (148)(149)(150) and craving (151) by targeting EF and self-regulation. Cognitive remediation has been shown to improve cognition in domains of working memory (WM), verbal memory, verbal learning, attention, and processing speed (151)(152)(153)(154).…”
Section: Cognitive Remediationmentioning
confidence: 99%